2013
DOI: 10.1186/1471-2458-13-228
|View full text |Cite
|
Sign up to set email alerts
|

An indigenous approach to explore health-related experiences among Māori parents: the Pukapuka Hauora asthma study

Abstract: BackgroundThe prevalence of asthma for Indigenous New Zealand Māori is amongst the highest in the world. Recent evidence shows ethnic differences in asthma symptom prevalence in New Zealand have widened, with asthma symptoms and hospitalisation rates consistently higher for Māori across all age-groups, especially children and adolescents. This paper: outlines our qualitative, longitudinal research exploring the practical issues Māori children and their families face trying to achieve optimum asthma outcomes; d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0

Year Published

2017
2017
2109
2109

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(91 citation statements)
references
References 41 publications
1
90
0
Order By: Relevance
“…This involvement in the data collection process also promotes a sense of ownership over the data, which is important in research with Indigenous Peoples and particularly CBPR (Castleden et al, 2008). Jones, Ingham, Cram, Dean, and Davies (2013) also indicated that photovoice is useful in traversing the divide that is presented between researchers and the Indigenous Peoples with whom they collaborate.…”
Section: General Indigenous Frameworkmentioning
confidence: 99%
“…This involvement in the data collection process also promotes a sense of ownership over the data, which is important in research with Indigenous Peoples and particularly CBPR (Castleden et al, 2008). Jones, Ingham, Cram, Dean, and Davies (2013) also indicated that photovoice is useful in traversing the divide that is presented between researchers and the Indigenous Peoples with whom they collaborate.…”
Section: General Indigenous Frameworkmentioning
confidence: 99%
“…It is similarly found in other cultures such as Latino (la familia; Desai et al, 2016), Mexican (familismo; Arcoleo et al, 2015), and Māori (whānau; Jones, Ingham, Cram, Dean, & Davies, 2013). In these cultures, the family is the primary source of social relationships and assistance crucial to one's sense of identity and self-worth (Desai et al, 2016;Jones et al, 2013). Family support (Scheckner, Arcoleo, & Feldman, 2015) and higher levels of family connectedness and stronger ethnic identity appear to be protective factors against asthma-related limitations (Koinis-Mitchell et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…It is similarly found in other cultures such as Latino (la familia; Desai et al, 2016), Mexican (familismo; Arcoleo et al, 2015), and Māori (whānau; Jones, Ingham, Cram, Dean, & Davies, 2013). In these cultures, the family is the primary source of social relationships and assistance crucial to one's sense of identity and self-worth (Desai et al, 2016;Jones et al, 2013).…”
Section: Discussionmentioning
confidence: 87%
“…Distinctive challenges related to geographic barriers contribute to the uncertainty experience for native Hawaiian parents living on rural islands. Aboriginal peoples (First Nations, Inuit, and Métis) of Canada (Watson et al, 2012), indigenous New Zealand Māori (Jones, Ingham, Cram, Dean, & Davies, 2013), and Aborginal and Torres Strait Islander people of Australia (Giarola et al, 2014) live in remote areas and encounter similar geographic barriers to hospitals and spirometry testing (Castleden et al, 2016), social and health services (Ely & Gorman, 2010), specialty medical services (Chang et al, 2000), and asthma education and support (Watson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%